Primary and secondary aqueous two-phase systems composed of thermo switchable polymers and bio-derived ionic liquids. (December 2017) - Song, Cher Pin; Ramanan, Ramakrishnan Nagasundara; Vijayaraghavan, R.; MacFarlane, Douglas R.; Chan, Eng-Seng; Coutinho, João A.P.; Fernandez, Luis; Ooi, Chien-Wei
Highlights: LLE data of PPG 400 + [Ch][AA] + water systems at different temperatures were determined. Salting-out coefficients of [Ch][AA]s were determined using Setschenow-type equation. Thermodynamics of the ATPSs were evaluated using e-NRTL model. Secondary ATPS was formed via thermo-separation of (PPG 400)-rich top phase from primary ATPS. Abstract: The liquid-liquid equilibrium (LLE) data for aqueous two-phase systems (ATPSs) comprising poly(propylene glycol) 400 (PPG 400) and cholinium-aminoate-based ([Ch][AA]) ionic liquid were determined experimentally at T  = (288.15 and 308.15) K, while the LLE data at T  = 298.15 K was adopted from our previous work for comparison. The experimental binodal data were satisfactorily fitted to a temperature-dependent nonlinear empirical expression. The reliability of tie-line data was confirmed by fitting the experimental data with the Othmer-Tobias and Bancroft equations. Furthermore, for the first time, the electrolyte nonrandom two-liquid model (e-NRTL) was used to correlate the tie-line data of PPG 400 + [Ch][AA] + water systems. The correlations of LLE data using these models provide a good description of the experimental values. The effect of temperature on the phase-forming capabilities of the corresponding [Ch][AA] was assessed using the experimental binodal data and the salting-out coefficient ( k 2 ) derived from the Setschenow-type equation. The values of k 2 were well correlated to the phase-forming abilities of [Ch][AA], and were found to increase at higher temperature. Upon heating to 308.15 K, the solution of (PPG 400)-rich top phase from the primary PPG 400 + [Ch][AA] + water systems formed the secondary ATPSs. The LLE data of the secondary PPG 400 + [Ch][AA] + water systems was also determined. The PPG 400 was concentrated in the top phase of the secondary ATPS; this could serve as a means to recover PPG 400 from the primary ATPS via the formation of secondary ATPS.